Four propositions on how to conceptualize, research, and develop teacher educator professionalism - Vanassche, Eline (Frontiers in Education, 2022)
This article offers four propositions on how to conceptualize, research, and develop teacher educator professionalism. These propositions start from one central thesis: teacher educator professionalism can only be fully understood by looking at actual teacher education practices and how these unfold and develop. Based on this conception of enacted professionalism, the first proposition questions the emphasis on teaching experience for teacher educators; the second proposition advances the idea that teacher education cannot be envisioned without someone to educate; the third proposition suggests making the teacher education institute as an organization a central focus of understanding; the fourth proposition addresses the need to reframe traditional forms of knowledge (re)presentation. In conclusion, a framework for future research and practice of teacher educator development is proposed.